PENGARUH BRAND IMAGE DAN BRAND TRUST TERHADAP KEPUTUSAN PEMBELIAN (Studi Pada Pengguna Smartphone Samsung di Fakultas Ekonomi dan Bisnis Universitas Islam Malang) - Ubaidillah Ubaidillah; N. Rachma (E-JRM : Elektronik Jurnal Riset Manajemen, 2019)
ABSTRACTThis study aims to examine and analyze the influence of brand image and brand trust on purchasing decisions among students of the Faculty of Economic Islamic University of Malang. The population and samples were taken from 96 Faculty of Economics student. Data collection can be through questionnaires and direct interviews with respondents. Analysis of thi data using SPSS version 16. Sampling using purposive sampling method and data testing techniques used in this study include validity test, reliability test, classic assumption test and multiple linear regression analysis and testing the research hypothesis.The results of the analysis show that there is a partial effect of brand image and brand trust and simultaneously on the decision to purchase Samsung smartphones in the student Faculty of Economic & Business, Malang Islamic University.Keywords : brand image, brand trust, and buying decision.